2021
DOI: 10.3389/fonc.2021.670804
|View full text |Cite
|
Sign up to set email alerts
|

Repositioning of Antiparasitic Drugs for Tumor Treatment

Abstract: Drug repositioning is a strategy for identifying new antitumor drugs; this strategy allows existing and approved clinical drugs to be innovatively repurposed to treat tumors. Based on the similarities between parasitic diseases and cancer, recent studies aimed to investigate the efficacy of existing antiparasitic drugs in cancer. In this review, we selected two antihelminthic drugs (macrolides and benzimidazoles) and two antiprotozoal drugs (artemisinin and its derivatives, and quinolines) and summarized the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 195 publications
(163 reference statements)
0
15
0
Order By: Relevance
“…Although some studies have shown these autophagy inhibitors to have promising effects in patients with intractable disease, side effects such as retinopathy and gastrointestinal problems due to agents such as hydroxychloroquine and chloroquine are an issue, and the appropriate indications for these drugs are not yet determined (Deng et al, 2019;Mulcahy and Thorburn, 2020;Uberall et al, 2019). An increasing number of studies have found that attenuated parasites (Zhou et al, 2019), blood-stage malarial parasites (Liu et al, 2017), anti-parasitic agents (Li et al, 2021;Lin et al, 2016;Vatsveen et al, 2018), and parasite proteins (Lopez et al, 2010;Ramirez-Toloza et al, 2020) had anti-tumor activity in various tumor models. These reports point to the possibility of identifying anti-tumor strategies from the perspective of parasites.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have shown these autophagy inhibitors to have promising effects in patients with intractable disease, side effects such as retinopathy and gastrointestinal problems due to agents such as hydroxychloroquine and chloroquine are an issue, and the appropriate indications for these drugs are not yet determined (Deng et al, 2019;Mulcahy and Thorburn, 2020;Uberall et al, 2019). An increasing number of studies have found that attenuated parasites (Zhou et al, 2019), blood-stage malarial parasites (Liu et al, 2017), anti-parasitic agents (Li et al, 2021;Lin et al, 2016;Vatsveen et al, 2018), and parasite proteins (Lopez et al, 2010;Ramirez-Toloza et al, 2020) had anti-tumor activity in various tumor models. These reports point to the possibility of identifying anti-tumor strategies from the perspective of parasites.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have shown these autophagy inhibitors to have promising effects in patients with intractable disease, side effects such as retinopathy and gastrointestinal problems due to agents such as hydroxychloroquine and chloroquine are an issue, and the appropriate indications for these drugs are not yet determined [16,22,23]. An increasing number of studies have found that attenuated parasites [24], blood-stage malarial parasites [25], anti-parasitic agents [26][27][28], and parasite proteins [29,30] had anti-tumor activity in various tumor models. These reports point to the possibility of identifying anti-tumor strategies from the perspective of parasites.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, inhibiting metastasis progression is the main focus of melanoma treatment [ 31 ]. There is increasing evidence that benzimidazole can be used as a source of antitumor agents as a repositioned drug for cancer therapeutics [ 22 ]. As the most well-studied antiparasitic agent, ABZ has already been validated in a few tumor models [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that benzimidazole can be used as a source of antitumor agents as a repositioned drug for cancer therapeutics [ 22 ]. As the most well-studied antiparasitic agent, ABZ has already been validated in a few tumor models [ 22 ]. However, no reports are available regarding the effect of ABZ on the EMT process of melanoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation